Does Mobility Increase the Productivity of Inventors? - Karin Hoisl (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2007)
Although labor mobility has been recognized as a key mechanism for transferring tacit knowledge, prior research on inventors has so far hardly discussed the impact of a move on inventive performance. Additionally, existing research has neglected the differences in gains from a move between high and lower performing inventors. This paper adds to the current R&D literature by presenting a jointly estimated quantile regression to compare the coefficients of the explanatory variables at different points of the performance distribution. Additionally, dummy variables are used to compare inventive performance prior and in the aftermath of a move. Results reveal that inventors at the upper end of the performance distribution are better able to benefit from a move to draw level with or to overtake non-movers in the post-move period. Whereas at the bottom of the performance distribution a higher level of education has a positive impact on inventive performance, education does not matter significantly at the upper end of the performance distribution. Data for the analysis was derived from a survey of German inventors (N = 3,049).
urn:nbn:de:bvb:19-epub-2023-9
Keywords: M54; O32; 650; Inventor; Mobility; Quantile Regression; Patent